Penggunaan pencahayaan semula jadi biophilia untuk mengurangkan pendedahan spektrum biru dalam bilik gelap terhadap kualiti tidur kanak-kanak. - Ahmad, Nur Atiqah; Zakaria, Safial Aqbar (ARTEKS : Jurnal Teknik Arsitektur, 2023)
Technology plays an essential role in people's lives, and gadgets have become a prevalent trend for information and communication. However, excessive gadget use among children can have negative side effects. Children often spend extended periods of time engaged with gadgets, disregarding screen brightness and maintaining a close distance to the screen. Some parents resort to gadgets as a quick way to pacify their children during tantrums. To address the challenges posed by advanced technology, this study aims to observe and interview parents with children aged 5 to 12. According to UC Davis Health in California, blue light, which is emitted by electronic devices, has the shortest wavelength and the highest energy. It can disrupt the production of melatonin, the hormone that regulates sleep. Exposure to blue light in a dark room, such as when children use electronic devices at night, further disrupts their sleep patterns. To mitigate this, the study will explore the implementation of biophilic natural lighting, which mimics the lighting found in nature. The goal is to create a harmonious and healthier environment that connects children with the natural world, promoting their well-being. By conducting a case study involving workers in biophilic and non-biophilic environments and a dark room is not an ideal choice for playing with gadgets, the study aims to investigate how biophilic natural lighting can reduce the exposure to blue spectrum in dark rooms, particularly for children. The ultimate objective is to determine the impact of biophilic natural lighting on children's sleep quality and propose effective lighting strategies to improve their overall sleep quality. The results of this study will demonstrate the significant improvement in children's sleep quality with the implementation of biophilic natural lighting, providing valuable design guidelines for creating healthier environments for children.